(3ebGUO GdYhGdi HbdGFO GddBdis - (3GHi YHO Gddg TeS GdOjf eMeO Hf SdjeGf Hf GdaGS GdQhOGfi(B( (3GdQOGfi (B) (3GdShS Gdecjs; (3eMeO Hf eMeO Hf SdjeGf Hf GdaGSj Hf WGgQ GdShSj GdQhOGdj GdeZQHj,J (B1094 (3g` s
(3ChdgG (B:s
(3jbhd GdMeO ddg MeOkG jheG ai fYeg GeG HYO agPg fHPg dWjaI GfJgHfGgG ef GjOi GdReGf HMeO ef GOQLfG ai MRHg hde jRd jQaYfG dbQjg s
(3BNQgG (B:s
(3hgPG LOhd jONd ai CYdGg HGdaVd HYO WQM GdSfjf GdfGbUI GdjROLQOjI HGdSHYjI hJONd ef WhdI HGdTgQ GdPi CQOJ eONd hdjcf gPG BNQ GdMOjK ai GdJhGQjN s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG LOGhds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B221s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B610 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B691 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs